Pengaruh Set Kesempatan Investasi Terhadap Hubungan Antara Kepemilikan Manajerial dan Aliran Kas Bebas dengan Tingkat Leverage Perusahaan - Endang Raino Wirjono (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2009)
Agency theory mentions that leverage (debt) is one of mechanism used by shareholders to minimize agency problem with manager. In this context, previous researchers show that leverage was influenced by free cash flow and insider ownership (managerial ownership). This research aims to examine the determinants of leverage in a research model and treats investment opportunity set (IOS) as moderating variable that will influence the relationship between free cash flow and managerial ownership with leverage. By using sample consist of 38 manufacturing companies, result from moderated Regression Analysis (MRA) statistically shows evidence that IOS influences the relationship between free cash flow and leverage. This result supported Tarjo’s research (2002).